The Functional Haplotypes of CHRM3 Modulate mRNA Expression and Associate with Bladder Cancer among a Chinese Han Population in Kaohsiung City. (7th December 2016) - Wang, Chiang-Ting; Chen, Tsung-Ming; Mei, Chien-Tai; Chang, Chun-Feng; Liu, Li-Lian; Chiu, Kuo-Hsun; Wu, Tsung-Meng; Lan, Yu-Ching; Liu, Wen-Sheng; Chen, Ya-Huey; Lin, Yi-Mei Joy
Abstract : Bladder cancer is one of the major cancer types and both environmental factors and genetic background play important roles in its pathology. Kaohsiung is a high industrialized city in Taiwan, and here we focused on this region to evaluate the genetic effects on bladder cancer. Muscarinic acetylcholine receptor M3 (CHRM3) was reported as a key receptor in different cancer types. CHRM3 is located at 1q42-43 which was reported to associate with bladder cancer. Our study attempted to delineate whether genetic variants of CHRM3 contribute to bladder cancer in Chinese Han population in south Taiwan. Five selected SNPs (rs2165870, rs10802789, rs685550, rs7520974, and rs3738435) were genotyped for 30 bladder cancer patients and 60 control individuals and genetic association studies were performed. Five haplotypes (GTTAT, ATTGT, GCTAC, ACTAC, and ACCAC) were found significantly associated with low CHRM3 mRNA level and contributed to increased susceptibility of bladder cancer in Kaohsiung city after rigid 10000 consecutive permutation tests. To our knowledge, this is the first genetic association study that reveals the genetic contribution of CHRM3 gene in bladder cancer etiology.